Proyecto de gestión de servicios para personas con discapacidad en Ventanilla - Figueroa, Jacqueline (2008)
This article presents the problem of the large number of people with disabilities in Mi Perú, Ventanilla, in addition to their limited access to health services, rehabilitation, and physical and psychological therapy, which is an issue of utmost importance due to the inaccessibility posed by the distance to these services and to the scarce economic resources of its people. There is a project that aims at the main socio-economic inclusion of the disabled people through their access to the services they need by improving such services in their towns. This project has three components: a) training in the care and attention, b) adequate equipment infrastructure in the rehabilitation centers and c) strengthening of management personnel within the framework of an agreement between the Municipality of Ventanilla and the Health Ministry, under which the municipality bears the cost of the center, and the ministry be responsible for the salaries of administrative and health personnel.